2023
DOI: 10.1001/jamanetworkopen.2023.0813
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Survival of Patients With Cancer From Their Initial Oncology Consultation Document Using Natural Language Processing

Abstract: ImportancePredicting short- and long-term survival of patients with cancer may improve their care. Prior predictive models either use data with limited availability or predict the outcome of only 1 type of cancer.ObjectiveTo investigate whether natural language processing can predict survival of patients with general cancer from a patient’s initial oncologist consultation document.Design, Setting, and ParticipantsThis retrospective prognostic study used data from 47 625 of 59 800 patients who started cancer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Our patient selection was the same as in prior work 55 . Of the 59,800 BC Cancer patients, we excluded 2784 due to starting cancer care multiple times, and 9391 due to not having a medical or radiation oncology consultation within 180 days of their cancer diagnosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our patient selection was the same as in prior work 55 . Of the 59,800 BC Cancer patients, we excluded 2784 due to starting cancer care multiple times, and 9391 due to not having a medical or radiation oncology consultation within 180 days of their cancer diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…Two types of neural models, CNN and LSTM, outperformed the simpler BoW models. This suggests these predictions may benefit from a more complex understanding of language made possible by neural networks, in contrast to related work using similar data and techniques to predict the survival of patients with cancer survival 55 . While we could not find similar work to which we could compare these results, these metrics are comparable to or better than other applications of ML for predicting future events in psychiatry, such as predicting whether a patient’s depression will respond to an antidepressant 56 , 57 , whether someone will complete or attempt suicide 58 , or if a child will later develop a bipolar disorder 59 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon conducting a prognostic investigation on 47,625 individuals with cancer, it was found that natural language processing can proficiently estimate their survival rates through traditional and neural models [36]. The outcomes were as good as or superior to previous research, signifying its viability for practical usage in predicting the endurance of patients with cancer.…”
Section: Predictive Modeling Of Cancer Characterizationmentioning
confidence: 94%
“…A growing number of NLP-based methods have recently been gaining popularity for their ability to predict patients' survival based on their clinical records and for facilitating efficient analyses of highdimensional scRNA-seq data [16][17][18][19] . For instance, Nunez et al 16 employ language models to predict the survival outcomes of breast cancer patients based on their initial oncologist consultation documents. Similarly, in the domain of scRNA-seq analysis, scETM 18 uses topic models to infer biologically relevant cellular states from single-cell gene expression data.…”
Section: Introductionmentioning
confidence: 99%